Development of system dynamic model to evaluate the impact of feed - in tariff for different energy resources - Shahmohammadi, Mohammad Sadegh (2015)
Malaysia has abundant potential of renewable energy resources and several renewable energy programs have been introduced by the government since the 1980s. However, comparing the real electricity generation capacity with the determined targets shows that results fell far short of the targets. Since 2001, more serious efforts were made in renewable energy development but the outputs were still not satisfactory by the end of the 9th Malaysia Plan in 2010. Therefore, the Feed-in Tariff mechanism which is known to be the most effective fiscal incentive for the expansion of renewable energy utilization was introduced in the Malaysia's National Renewable Energy Policy and Action Plan has been applied since 2011 for electricity generation from Solar, Small-Hydro, Biogas, Biomass and Municipal Solid Waste resources. Solar PV has the highest FiT rate with a range of 1.25-1.75 RM/kWh and Small-Hydro has the least rate with 0.23-0.24 RM/kWh. FiT duration for Solar PV, Municipal Solid Waste and Small-Hydro resources is 21 years while it is 16 years for Biomass and Biogas resources. Having said that, assigning inappropriate FiT rates or degression rates may result in a backfire. Hence, in this study, a broad range of data was gathered to develop a comprehensive system dynamics model to evaluate the impacts of Feed-in Tariff mechanism on the generation mix of Malaysia during a 20-year period between 2011 and 2030. The causal diagram was developed first to point out the causal relationships between the different variables of the model and to determine the system boundaries. Then ten subsystems were defined to establish the stock and flow diagram. High complexity of the system with several feedback loops and interrelationships between the variables was the main reason of applying system dynamics approach in this study. The model was ran in two different scenarios of "Business as Usual" and "Feed-in Tariff". Accordingly, the results of the model were extracted for each scenario and compared with each other. Outputs of the Feed-in Tariff scenario were also compared with the determined targets of Malaysia's national renewable energy policy and action plan in terms of environmental and economic factors. Results demonstrated that although the new policy may lead to a satisfactory level of target achievement, the Malaysian government may face an increasing shortage in its renewable energy fund budget starting around 2019; unless it increases its income sources by raising the surcharges on electricity bills and / or decreases its expenditures by optimizing the amount of Feed-in Tariffs in different periods. Sensitivity analysis illustrated that more funding will not lead to a more sustainable generation mix unless it is paid at the right time and in the right direction. Grid parity is also forecasted for different resources as an intermediate outcome of this study. Using this model, policymakers can carry out analysis to determine the amount of money that must be collected from the electricity consumers through the surcharges on electricity bills as well as the amount of Feed-in Tariff to be paid for different renewable resources in different periods.